Influence of the Addition of Al2O3 Nanoparticles and the Duration of Pressing on the Physical Properties of OSB Panels - Lima, Felipe O. [UNESP]; Silva, Luana Cristal L. [UNESP]; Ferreira, Bruno S. [UNESP]; de Morais, César Augusto G. [UNESP]; Bertolini, Marília da S. [UNESP]; Barreiros, Ricardo M. [UNESP]; Azambuja, Maximiliano Dos A. [UNESP]; Caraschi, José Claudio [UNESP]; Favarim, Higor R. [UNESP]; Campos, Cristiane I. [UNESP] (BioResources, 2022)
For greater durability, materials must withstand contact with water, making it difficult for biodegrading agents to attack. The present study produced and evaluated the heat transfer for two pressing times and the physical properties of OSB panels, produced with pinewood strands and Al2O3 nanoparticles addition. The nanoparticles were synthesized through the sol-gel-protein method and added to the resin in the proportion of 0.5%. During the pressing process, heat transfer and distribution in the central region of the particle mat were evaluated using a type K thermocouple. After its fabrication, the panels were characterized to evaluate density, moisture content, thickness swelling, and water absorption. The results obtained indicated that the nanoparticle addition caused a refractory effect in the central region of the mat, leading to a small reduction in the pressing temperature for the 600 s cycle. However, there was no compromise in resin cure, indicating good interaction of the panels with nanoparticles in water contact, for both pressing times. There was an improvement in the panel thickness swelling with the addition of 0.5% of Al2O3 nanoparticles, with all properties meeting the Class 1 indicators of the EN 300 (2006) standard.
Keywords: Heat transfer; Nanotechnology; Oriented strand board; Thickness swelling; Wood